Bird diversity and ethno-ornithological knowledge of local people in Ciletuh-Palabuhanratu Geopark, Sukabumi, West Java, Indonesia - JOHAN ISKANDAR; SYAHRAS FATHIN A; HASNA SILMI R; TEGUH HUSODO; INDRI WULANDARI; ERRI N. MEGANTARA; RUHYAT PARTASASMITA; SYA SYA SHANIDA (Society for Indonesian Biodiversity, 2021)
Abstract. Iskandar J, Fathin AS, Silmi RH, Husodo T, Wulandari I, Megantara EN, Partasasmita R, Shanida SS. 2021. Bird diversity and ethno-ornithological knowledge of local people in Ciletuh-Palabuhanratu Geopark, Sukabumi, West Java, Indonesia. Biodiversitas 22: 3409-3422. Birds have ecological and social functions, and are common to be used as bioindicators of environmental changes. Birds are very important consideration when establishing conservation areas, including geopark which has uniqueness in terms of geological, biological and cultural diversities. This study aimed to investigate the bird diversity in Ciletuh-Palabuhanratu Geopark, West Java, Indonesia and as well as to reveal the local knowledge on bird species and folk classification, functions and utilization of birds among the village people. Mixed methods of quantitative and qualitative approaches were applied in this study, while some techniques, including semi-structured interviews, structured interviews, and bird observation on transect and spotlighting were employed to collect the primary data. In total, there were 121 bird species of 47 families of which 88 species were recorded during the field observation and 79 species were documented through the interviews with respondents. Among them, 12 species are listed as having high conservation status under IUCN, 17 species are listed as Appendix II (CITES), and 21 species are listed by Regulation of the Minister of Environment and Forestry of the Republic Indonesia No. P 106/2018 on Protected Plant and Animal Species. The local community has profound knowledge of birds species, folk classification, ecological, socio-cultural, and socio-economic functions. In the past, the village people had traditional beliefs and myths on birds, resulting in some sacred birds had been traditionally conserved. Nowadays, these are no longer strongly existed, and consequently, many birds have been hunted by using different methods of hunting birds, both traditional and modern for various purposes, including for consumption, bird keeping, and trading to obtain cash. Therefore, bird conservation efforts that involve the community are really needed in this area as the strategy of sustainable management of Ciletuh-Palabuhanratu Geopark.